Tantangan dan Peluang Partisipasi Masyarakat Menengah ke Bawah dalam Proses Politik dan Pemerintahan di Bandung - Johana Andriani Nainggolan; Julia Ivanna (Departement of Mathematics Education, 2024)
Community participation in political and government processes is the main pillar in building a healthy and sustainable democracy. Participation of the lower middle class in the political and government process in the city of Bandung is an important focus in efforts to build a democratic and inclusive government. Challenges such as limited access to information and economic factors have hampered their participation, but there are also opportunities that can be exploited, such as advances in information technology and community empowerment programs. The type of research used is qualitative through literature study and field study. Qualitative research methods are research methods used to explain a phenomenon in depth. Through literature research and field surveys, it was found that local governments, NGOs and communities need to work together to overcome these challenges and take advantage of existing opportunities. Therefore, increasing the participation of the lower middle class community in Bandung is not an easy thing, but is an important step to build a more inclusive, competitive and just society. Through continued cooperation, Bandung has the potential to become an inspiring example of how to strengthen community participation in political processes and governance and create a better future for all citizens.